ANALISIS YURIDIS STATUS HARTA BERSAMA AKIBAT PEMBATALAN PERKAWINAN - Rachman, Aulia; Sy, Najmi Fahriah (Mitsaq: Islamic Family Law Journal, 2023)
ABSTRACT There is an application for annulment of marriage filed by the first wife against the husband's marriage with the second wife, where it is legal to apply according to the applicable laws and regulations and of course has legal consequences for him, one of which is property. This refers to the Marriage Law No. 1 1974 article 22 paragraph (2) point b, this becomes a problem later considering that marriages have been going on which of course have produced a lot of joint assets but are considered non-existent when the annulment is made, and also the large number of cases of marriage annulment which the researcher is interested in studying. Whereas with the intention to describe the juridical analysis of the status of joint property as a result of marriage annulment. Using a qualitative research method with an empirical-normative approach, based on observational data and interviews as well as observations of the decisions of the Tenggarong Religious Court. The following research results obtained are that first, the judge's considerations in deciding the decision case Number: 1252/Pdt.G/2020/PA.Tgr are based on the Marriage Law No. 1 of 1974, Compilation of Islamic Law, as well as fiqh principles, assemblies the judge decided the case in the annulment of the marriage in which the Petitioner (as the first wife) who filed a case for the annulment of the marriage against her husband, has the right to regain her husband's rights and responsibilities. Second, the status of shared assets in the decision Number: 1252/Pdt.G/2020/PA.Tgr which is considered nothing which in this case becomes the right of the first wife in accordance with the contents of Article 22 paragraph (2) point b, which applies retroactively to assets together as a result of the law of marriage annulment caused by a previous marriage. And based on MA circular letter Number 2 of 2019 point f where there are no legal consequences in the form of zaujiyah maintenance, joint assets and inheritance in second, third and fourth marriages if the marriage is carried out without court permission and not in good faith.